Implementasi Metode Scrum Agile Dan Analisis Return On Investment (ROI) Pada Sistem Informasi Perpustakaan - Muhammad Hafiz Ar Rahman; Muhammad Husni Rifqo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The library is one of the important institutions that provide and manage information to support learning, teaching, and research activities. In its development, the need for an integrated and efficient library information system is increasing, along with the demands of digitizing services and managing data quickly and accurately. This research aims to implement the Agile Scrum method in the development of Library Information Systems and conduct a return-on-investment (ROI) analysis to measure the effectiveness of the investment from a business and economic perspective. Based on the research problem raised and the results of the research that has been conducted, it shows that the Scrum method is proven to be effective in increasing flexibility and responsiveness to user needs. Key features are completed on time, and user feedback can be responded to in the next sprint. Active collaboration minimizes the risk of errors and maintains system quality. The first-year ROI is positive although small (4.65%), but the system is sustainable, so the ROI will increase significantly in years 2 and 3 because costs remain low while benefits continue to grow.